Rational Design of Matrix Metalloproteinase-13 (MMP-13) Activatable Probes for Enhanced Specificity - Zhu, Lei (2013)
Due to the important roles of matrix metalloproteinases (MMPs) play in tumor invasion and metastasis, various activatable optical probes have been developed to visualize MMP activities in vitro and in vivo. Our recently developed MMP-13 activatable probe, L-MMP-P12, has been successfully applied to image the expression and inhibition of MMPs in a xenografted tumor model (Zhu L et al., Theranostics. 2011;1:18–27). In this study, to further optimize the in vivo behavior of the proteinase activatable probe, we tracked and profiled the metabolites by a high resolution LC/MS system. Two major metabolites that contributed to the fluorescence recovery were identified: One was specifically cleaved between Glycine (G(4)) and Valine (V(5)) by MMP, while the other one was generated by non-specific cleavage between Glycine (G(7)) and Lysine (K(8)). In order to visualize the MMP activity more accurately and specifically, a new probe D-MMP-P12 was designed by replacing the L-lysine with D-lysine in the MMP substrate sequence. The metabolic profile of the new probe, D-MMP-P12, was further characterized by in vitro enzymatic assay and no non-specific metabolite was found by LC/MS. Our in vivo optical imaging also demonstrated that D-MMP-12 had significantly higher tumor-to-background ratio (TBR, 5.55 ± 0.75) compared with L-MMP-P12 (3.73 ± 0.31) at 2 h post-injection. The improved MMP activatable probe may have the potential for drug screening, tumor diagnosis and therapy response monitoring. Moreover, our research strategy can be further extended to study other protease activatable probes.